Geografia, Trabalho Social e Design: trabalho interdisciplinar e diálogo de saberes na interligação com o meio para a mudança eco-sócio-territorial - Mansilla–Quiñones, Pablo (Universidad Nacional del Litoral, 2021)
The work of Geography and related fields of the social sciences have undertaken important challenges in the last decade in search of a significant link and commitment to society, decolonial and counter–hegemonic, transforming territorial discourse and practices. In the social sciences, a spatial turn is being recognised, and a drive towards the promotion of eco–socio–territorial change. The field of design emerges as a hinge that connects these epistemological turns, and at the same time makes them tangible through the creation of interface devices for the interactive communicative flow that shapes the experience. We present several cases of practical application of interdisciplinary experiences carried out in the framework of a rhizomatic search to connect the work of the disciplines of Geography, Social Work and Design at the Pontificia Universidad Católica de Valparaíso, Chile, in which we project a link with the environment from the dialogue of knowledge, recognising and developing university actions in the territories from the value of the knowledge carried by the different actors, and the development of a work of greater commitment to reality in pursuit of its replicability and capacity for eco–socio–territorial transformation.